2023
DOI: 10.1007/s00167-023-07557-y
|View full text |Cite
|
Sign up to set email alerts
|

High body mass index is not a contraindication for an arthroscopic ligament repair with biological augmentation in case of chronic ankle instability

Kevin Guiraud,
Gustavo Araujo Nunes,
Jordi Vega
et al.

Abstract: Purpose Obesity remains frequently mentioned as a contraindication for lateral ankle ligament repair. The aim of the study was to compare the clinical results of an arthroscopic lateral ligament repair with biological augmentation between patients with a body mass index (BMI) of more than 30 and less than 30. Methods Sixty-nine patients with an isolated lateral ankle instability were treated with an arthroscopic anterior taloibular ligament (ATFL) repair with biological augmentation using the inferior extensor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…In young athletes, like the baseball players in one of the studies, significant improvements in ankle range of motion and pain reduction were observed post-manipulation (Fryer, Mudge & McLaughlin, 2002). This finding was echoed in the study focusing on individuals with chronic ankle instability, where improved dorsiflexion was noted (Marrón-Gómez, Rodríguez-Fernández & Martín-Urrialde, 2015;Guiraud, et al, 2023). Particularly notable, is the suggestion from the study involving elite female handball players that manipulation might not only aid in rehabilitation but could also play a role in enhancing athletic performance, as evidenced by improved vertical jump heights (Hedlund et al, 2014).…”
Section: Discussionmentioning
confidence: 90%
“…In young athletes, like the baseball players in one of the studies, significant improvements in ankle range of motion and pain reduction were observed post-manipulation (Fryer, Mudge & McLaughlin, 2002). This finding was echoed in the study focusing on individuals with chronic ankle instability, where improved dorsiflexion was noted (Marrón-Gómez, Rodríguez-Fernández & Martín-Urrialde, 2015;Guiraud, et al, 2023). Particularly notable, is the suggestion from the study involving elite female handball players that manipulation might not only aid in rehabilitation but could also play a role in enhancing athletic performance, as evidenced by improved vertical jump heights (Hedlund et al, 2014).…”
Section: Discussionmentioning
confidence: 90%
“…In the present study, all surgical operations were performed in the safe zone [11], with only two patients (4.8%) in Group A complaining of knot irritation and one patient (3.1%) in Group B complaining of incision numbness at follow-up. To avoid SPN injury, the SPN was marked in case of its visibility [13]. Furthermore, the AM portal was established first, which was far from the nerve, and the AL and the acAL portals were made with transillumination.…”
Section: Discussionmentioning
confidence: 99%